2021
DOI: 10.1007/978-3-030-68948-3
|View full text |Cite
|
Sign up to set email alerts
|

Touch-Based Human-Machine Interaction

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Furthermore, the different orientations of the same applied force will also result in different responsivities, as the force closer to the perpendicular orientation will obtain more stress in the z-direction. In the study of [ 42 ], it was shown that the responsivity increases by 51% when the touch orientation increases from 30° to 90° as shown in Figure 7 .…”
Section: Conventional Applications and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the different orientations of the same applied force will also result in different responsivities, as the force closer to the perpendicular orientation will obtain more stress in the z-direction. In the study of [ 42 ], it was shown that the responsivity increases by 51% when the touch orientation increases from 30° to 90° as shown in Figure 7 .…”
Section: Conventional Applications and Discussionmentioning
confidence: 99%
“…According to the transmission speed and the timing of the mechanical waves, the touch location can be evaluated. However, it only provides 2-dimension information [ 42 ].…”
Section: Piezoelectric-based Touch Sensing Architecturementioning
confidence: 99%
See 3 more Smart Citations